2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--33339
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Across Boundaries: Examining the Institutional Process of Establishing Multidisciplinary Courses

Abstract: Virginia Tech. Through real-world engineering applications, Dr. Bairaktarova's experiential learning research spans from engineering to psychology to learning sciences, as she uncovers how individual performance is influenced by aptitudes, spatial skills, personal interests and direct manipulation of mechanical objects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In the literature, reports on multidisciplinary and interdisciplinary courses are not uncommon [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. However, the literature progressively becomes more and more scant for multidisciplinary and/or interdisciplinary courses that are focused on the graduate level [21,22,32,33], on interdisciplinary knowledge about complex systems and systems thinking [23,32,34], and on specific topics (e.g., renewable energy [29,33]).…”
Section: Multidisciplinary Coursesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, reports on multidisciplinary and interdisciplinary courses are not uncommon [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. However, the literature progressively becomes more and more scant for multidisciplinary and/or interdisciplinary courses that are focused on the graduate level [21,22,32,33], on interdisciplinary knowledge about complex systems and systems thinking [23,32,34], and on specific topics (e.g., renewable energy [29,33]).…”
Section: Multidisciplinary Coursesmentioning
confidence: 99%
“…Moreover, the authors discuss how their courses were designed to work within the constraints of typical graduate programs [35]. Along the same lines, Snyder et al have reported on different ways to navigate the institutional process of establishing multidisciplinary courses [37]. Indeed, these authors have reported that some faculty strategically use co-listing and co-teaching to fulfill curricular needs for multiple departments.…”
Section: Multidisciplinary Coursesmentioning
confidence: 99%